DEMOKRASI VERSUS DEMOKRASI: SWAPRAJA GOWA DAN PERMASALAHAN OTONOMI DAERAH DI PROVINSI SULAWESI PASCA PENYERAHAN KEDAULATAN DARI PEMERINTAH KOLONIAL BELANDA - Djunedding, Burhaman (JURNAL ILMU BUDAYA, 2023)
The main problems of the regional government in Indonesia after cession of sovereignty from the Dutch are the swapraja regions. Eventhough the swapraja region has been disbanded which is implied in regulation Peraturan Pemerintah Nomor 34 Tahun 1952 and the formation of seven autonomous regions in South Sulawesi, however those swapraja regions are still exist. The method used in this study is a historical method. The first step of this study is data collection technique and in History this is called heuristic. After primary and secondary sources are collected, the next step is data sorting. This process is known as source criticism. Keywords : Democracy, Swapraja Regions, and Regional Autonomy